Use of agroindustrial vegetable waste for the development of a seasoning with low sodium content - Mendez-Trujillo, Vianey; Ramos-Romero, Martha; Gonzalez-Mendoza, Daniel; Navarro-Ibarra, María; Reyes-Pavon, Diana (Revista Colombiana de Investigaciones Agroindustriales, 2024)
The revaluation of agricultural waste represents a source of generation of new products with a high content of bioactive compounds and low sodium content that can contribute to the reduction of the consumption of this element by the population. Therefore, the objective of the present study was to evaluate the antioxidant content, amount of sodium and phenolic compounds of three commercial seasonings with a vegetable seasoning formulated from garlic/onion residues. The results showed that it was possible to formulate a seasoning using garlic and onion peels dehydrated for 24 h at 50 °C. Which were ground to 300 microns and mixed in a proportion of 60 g of garlic powder with 40 g of onion powder. This seasoning was then compared to three commercial formulas. The analysis of the garlic/onion-based seasoning presented significantly lower values ​​of sodium (60 mg/ 100 g) and NaCl (4.7%) compared to the three commercial seasonings that showed sodium values ​​(137 mg/ 100 g; 69 mg/100 g and 237 mg/100 mg, respectively) and NaCl (54.8%, 33% and 70%, respectively). In contrast, the values ​​of proteins, phenolic compounds and antioxidant activity showed significantly higher values ​​compared to commercial seasonings. Finally, our study shows the generation of a formulation of a seasoning low in sodium and with important values ​​of bioactive compounds, with a technology accessible to producers. This allows us to generate viable alternatives for the revaluation of onion and garlic peels, promoting their sustainable management. Future studies should identify the effect of extracts of this mixture on the inhibition of enzymes related to blood pressure. Which would contribute to the incorporation of this product in the development of additives with low sodium intake for the population.